Late Pleistocene skeleton of Canis lupus 1., 1758 from Grotta Mora Cavorso (Jenne, Latium, central Italy) - Gatta, M; Petronio, C; Salari, L; Silvestri, L.; ROLFO, MARIO FEDERICO (Comptes Rendus Palevol, 2016)
This paper describes the skeleton of Canis lupus found in Layer 7 of Grotta Mora Cavorso (Latium, central Italy), correlated with the MIS 3. Research on the deposition dynamics of this find is still in progres, but the action of human or other predactors can be excluded. The age at death was estimated at around six years old. Preliminary morphometric analyses and comparisions with samples of Italian Late Pleistocene wolf and extant Apennine wolf (C. lupus italicus) remains, show that the dimension of teeeth and long bones are among the biggest known from the Late Pleistocene and larger than the extant Apennine wolf.